'Even if you don't pay attention to it, you know it's there': A qualitative exploration of adolescents' experiences with digital food marketing. (1st September 2022) - Ares, Gastón; Antúnez, Lucía; de León, Carolina; Alcaire, Florencia; Vidal, Leticia; Natero, Virginia; Otterbring, Tobias
Abstract: Adolescents are particularly vulnerable to digital food marketing. However, research on adolescents' recall, awareness, and opinions of this type of marketing is still scarce. Accordingly, the present study aimed to conduct an in-depth examination of adolescents' experiences with digital food marketing. A convenience sample of 209 adolescents was recruited at two private educational institutions and a public health facility in Montevideo, the capital city of Uruguay. Semi-structured group interviews were conducted, recorded in audio and transcribed. The transcripts were analyzed using content analysis based on a deductive-inductive approach. Results showed that participants were highly exposed to digital food marketing, as they all remembered having seen advertisements, with those of fast-food restaurants and food-ordering apps being the most frequently mentioned. According to the adolescents' accounts, images, colors, music, oversized portions, product novelty, price promotions and celebrities were the most memorable aspects of food advertisements. Participants recognized the effect of advertisements on product awareness and wanting, and, to a lesser extent, on actual purchase and consumption behavior. Factors that were thought to mediate the impact of digital marketing on food choice were also identified. In the final part of the interviews, participants proposed strategies to reduce the effect of digital marketing on their food choices, which included both regulatory approaches to reduce exposure to digital marketing of unhealthy foods and behavior change communication. Together, the current findings provide insights for the development of multifaceted strategies to reduce the effects of digital food marketing on the eating habits of adolescents.